Biochemical and genetic characterization of Botrytis cinerea mutants resistant to the plant-derived pesticide trans-dehydromatricaria ester - Tang, Gaijuan; Nan, Rui; Dong, Hui; Wang, Yong; Guo, Wenhui; Ta, Yongquan; Han, Yunfei; Zhang, Chao; Wang, Yonghong (Frontiers in Plant Science, 2025)
Botrytis cinerea is one of the top ten plant pathogens worldwide, with a broad host range. In modern agricultural production, it is typically controlled using chemical agents. However, the overuse of chemical fungicides has led to environmental pollution and the development of drug-resistant strains, necessitating the search for new fungicides. Trans-dehydromatricaria ester (TDDE) not only enhances infectivity but also reduces lipid oxidation and improves osmotic regulation. Through the selection process using TDDE, seven highly resistant strains of B. cinerea with stable genetic traits were obtained. These resistant strains exhibited significant physiological alterations, including increased cell membrane permeability, heightened osmotic sensitivity, and perturbations in energy metabolism and lipid peroxidation. Additionally, TDDE had a negative cross-resistance with procymidone, but not with pyraclostrobin, boscalid and fluazinam. Resequencing and transcriptomic analysis identified six potential target genes, of which Bcin15g03240 and Bcin09g00290 are associated with membrane transport. Molecular docking revealed that Bcin15g03240 interacts with TDDE via hydrogen bonds. These findings offer preliminary insight into the molecular targets of TDDE’s antimicrobial activity. Overall, the results provided a crucial theoretical foundation for understanding TDDE’s mode of action against B. cinerea and for developing green pesticides based on these targets.